Screws with larger core diameter and lower thread pitch increase the stability of locked plating in osteoporotic proximal humeral fractures. (March 2019) - Schliemann, Benedikt; Risse, Nadine; Frank, Andre; Müller, Marcus; Michel, Philipp; Raschke, Michael J.; Katthagen, J. Christoph
Abstract: Background: Little is known about the screw design as a factor for stability of the bone-implant interface in locking plate fixation of proximal humeral fractures. Aim of the present study was to analyze if locking screws with a large core diameter and a low thread pitch provide increased stability when compared to conventional locking screws. Methods: 3-Part proximal humeral fractures were created in ten pairs of osteoporotic human cadaveric humeri and fixed with a locking plate. Head fixation was performed with screws with a large core diameter (soft bone screws) in one humerus and with conventional cancellous locking screws in the other humerus of each donor. Specimens were loaded in the varus bending position. Stiffness, failure loads, plate bending and motion at the bone-implant interface were evaluated using mechanical sensors and an optical motion capture system. Findings: The stiffness of the construct for the soft bone screws was 299.8 N/mm (IR, 72.1 N/mm) and 203.9 N/mm (IR, 37.3 N/mm) for the conventional locking screws ( p  = 0.005). Plate bending did not differ between the two groups. Motion at the bone-implant interface was significantly reduced in the soft bone screw group ( p  < 0.05). The median load-to-failure was significantly higher in the soft bone screw group (358 N vs. 313 N; p  = 0.012). Interpretation: The use of soft bone screws is associated with less motion at the bone-implant interface and therefore greater fixation strength when compared to fixation with conventional locking screws. Clinical studies are needed to prove these biomechanical findings in the in vivo situation. Level of evidence: Controlled laboratory study. Highlights: Locking plate fixation of proximal humerus fractures is associated with high failure rates. Medial support screws, screw augmentation and bone grafts are measures to increase the stability. The influence of screw design, i.e. core diameter and thread pitch, is not thoroughly understood. Screws with high core diameter and low thread pitch are tested against conventional locking screws. These new screws provide higher fixation strength and may be associated with lower failure rates.